Success in Academic Surgery: Clinical Trials - Pawlik, Timothy M.; Sosa, Julie A.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
Success in Academic Surgery: Clinical Trials is a unique and portable handbook that focuses on clinical trials. It includes new educational materials which are necessary to address not only the rapid evolution and rise of novel research methodologies in basic science and clinical/educational research, but also the changing environment for academic surgeons. Aimed at medical students, surgical residents and others considering a career within surgery, Success in Academic Surgery: Clinical Trials is a valuable text which offers practical guidance on developing a career within surgical education. Written by expert authors from around the world who are members of the AAS (Association for Academic Surgery), this book looks at all aspects of clinical trials, from trial design and building a research team to statistics and getting your trial published.
1. Building your Clinical Trial Research Team -- 2. Clinical Trials: Ensuring Quality and Standardization -- 3. Statistics - Setting the Stage -- 4. Clinical Trials: Handling the Data -- 5. Data Safety Monitoring Boards -- 6. Planning for Data Monitoring and Audits -- 7. The Budget -- 8. Regulatory Considerations in Human Subjects Research -- 9. Publishing a Clinical Trial -- 10. Device Versus Drug Clinical Trials: Similarities and Important Differences -- 11. Defining the Study Cohort: Inclusion and Exclusion Criteria -- 12. History of Clinical Trials -- 13. Ethics of Clinical Trials -- 14. Trial Design: Overview of Study Designs (Phase I, II, III, IV, Factorial Design).
Keywords: Medicine; Surgery; Medical Education; Medicine & Public Health; Medicine/Public Health, general; Surgery; Medical Education